Perancangan User Experience Aplikasi Jasa Jahit "Tailorku" untuk Membantu Masyarakat di Masa Pandemi - Devita Natalia Krisdayanti; Ratih Kartika Dewi; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Sewing is the work of connecting cloth, fur, animal skins, and other materials that a sewing needle and thread can pass through. Sewing can be done by hand using a hand needle or with a sewing machine (Toni, 2015). The community feels the impact of the government's implementation and restrictions, namely the difficulty of meeting needs that must be done directly so they have to move online. However, many things made sewing services less attractive to the public before the pandemic, namely various things, namely unknown or distant locations, less extensive orders consisting of only people around, sewing not according to consumer desires, and long sewing times. To overcome these problems, a mobile application is needed to help the community during the pandemic, so a solution is needed to help connect tailors and the wider community as potential customers. To realize this solution, the researcher proposes a sewing application solution design to help people find tailors according to their wishes and needs. This user experience design will later be carried out by designing a solution design in the form of a user experience which is designed based on the results of interviews with potential users using the Human-Centered Design method. The test uses Usability testing, namely the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). From the results of using usability testing on the design of my Tailorku application solution, the following results are obtained, the effectiveness value is 100%, efficiency is 0.145 goals/s and user satisfaction results get 82.5 with category A which means the adjective rating is Excellent. The next user experience test was using UEQ with the result that the attractiveness aspect got 2.28, the perspicuity aspect got 2.09, the efficiency aspect got 2.15, the dependability aspect got 2.09, and the stimulation aspect got 2.09, and the novelty aspect got 2.14.